Semiotic Analysis of Gender Representation in Film Traveler's Hijab: Love Sparks in Korea - Natasha, Rizkya Adelia; Salsyabila, Sarah; Tawang, Nur Asia (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
Films as part of mass media have a big impact on human life and tend to depict women as weak, helpless, and targets of crime. In the film